Studi Kritik Hadis tentang Kesehatan Mental - Mukoyah; Agus Suyadi Raharusun (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about mental health. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about mental health in the history of Tirmidhi No. 2268. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi with maqbul ma'mul bih qualifications for the practice of Islam in maintaining mental health by creating positive views for oneself and others. This study concludes that the hadith narrated by Tirmidhi No. 2268 is relevant to be used as a basis for maintaining mental health, namely getting closer to Allah SWT, dhikr, repenting, and always praying to Him, so that a Muslim person is formed with a positive outlook, both for oneself and for others.